Development of higher school students’ independence as a component of work culture (Pedagogy of Higher and Secondary Education, 2014)
Seryogina I. Y. Development of higher school students’ independence as a component of work culture.The article presents the ways of developing higher school students’ independence as a component of work culture; offers the methods of developing higher school students’ independence; reveals the dynamics of intensive, situational and occasional demonstration of students’ independence in their learning activities.
Keywords: work culture; independent activity; the method of sense regulation; professional development of students